STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEMBELAJARAN GURU BERBASIS TEKNOLOGI DI LINGKUNGAN MADRASAH - Muslimin, Fatkhul; Pratama, Putra Adi; Azizah, Siti Nur (Jurnal Manajemen Pendidikan, 2026)
The The study is motivated by the increasing importance of technological mastery among teachers as part of the demands of 21st-century education and digital transformation in learning processes. This research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation. The research informants consisted of the principal, an Aqidah Akhlak teacher, a Physics teacher, and a History teacher. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the principal's strategies to enhance teachers' technology-based learning competencies include educational technology training, workshops on digital learning media utilization, individual mentoring, and the establishment of teacher learning communities. The principal also provided support through the availability of technological facilities, internet access, and opportunities to participate in professional development activities. These strategies positively impacted teachers' competencies in utilizing technology for learning, including the use of digital media, online learning platforms, and technology-based assessment applications. Although challenges such as varying levels of digital literacy among teachers and limited time were identified, continuous mentoring and teacher collaboration proved effective in overcoming these obstacles.